2016
DOI: 10.7150/ijms.16810
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviate hypoxic pulmonary hypertension via anti-inflammation and anti-oxidant pathways in rats

et al.

Abstract: Resveratrol, a plant-derived polyphenolic compound and a phytoestrogen, was shown to possess multiple protective effects including anti-inflammatory response and anti-oxidative stress. Hypoxic pulmonary hypertension (HPH) is a progressive disease characterized by sustained vascular resistance and marked pulmonary vascular remodeling. The exact mechanisms of HPH are still unclear, but inflammatory response and oxidative stress was demonstrated to participate in the progression of HPH. The present study was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…The inhibitory effect of resveratrol on arginase II was PI3K-Akt signaling pathway-dependent [99]. Similar results were found in rat PASMC [100], in hypoxic pulmonary hypertension rats [101], and in monocrotaline-induced PAH [102].…”
Section: Flavonoids and Other Polyphenolssupporting
confidence: 81%
“…The inhibitory effect of resveratrol on arginase II was PI3K-Akt signaling pathway-dependent [99]. Similar results were found in rat PASMC [100], in hypoxic pulmonary hypertension rats [101], and in monocrotaline-induced PAH [102].…”
Section: Flavonoids and Other Polyphenolssupporting
confidence: 81%
“…Decreased apoptosis and increased autophagy Rat H9c2 cardiomyoblasts [94] questionable. However, resveratrol has been implicated as a cardioprotective drug for many cardiovascular diseases both in preclinical studies [121] and in man [122], and this is thought to be largely due to its anti-inflammatory and anti-oxidant action [123]. Of specific interest for the topic of this review, resveratrol has been shown to lead to activation of AMPK and to reduce cardiac fibrosis and hypertrophy in a mouse model of pressure overload by transverse aortic constriction [124].…”
Section: Resveratrolmentioning
confidence: 99%
“…The resultant product exhibited a distinct thin layer chromatographic signal from the reactants (data not shown). 1 HNMR was utilized to verify the chemical structure of the product. possesses a hydrophilic property, whereas the oleoyl moiety is hydrophobic.…”
Section: Synthesis and Identification Of N-oleoyld-galactosaminementioning
confidence: 99%
“…Resveratrol (RES) is a natural polyphenol which is rich in a variety of plants and fruits, such as grapes, peanut and mulberry. This compound has been shown of possessing multiple pharmacological and healthy benefits, including anti-inflammation/ oxidation, 1 antitumor, 2 and immunoregulation. 3 Currently, the French Paradox, a low incidence of cardiovascular diseases relative to a high saturated fats diet, makes this compound become popular.…”
Section: Introductionmentioning
confidence: 99%